2006
DOI: 10.1890/04-0329
|View full text |Cite
|
Sign up to set email alerts
|

Carryover Aquatic Effects On Survival Of Metamorphic Frogs During Pond Emigration

Abstract: In organisms with complex life cycles, physiological stressors during early life stages may have fitness-level impacts that are delayed into later stages or habitats. We tested the hypothesis that body size and date of metamorphosis, which are highly responsive to aquatic stressors, influence post-metamorphic survival and movement patterns in the terrestrial phase of an ephemeral pond-breeding frog by examining these traits in two populations of northern red-legged frogs (Rana aurora aurora). To increase varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 88 publications
10
134
0
Order By: Relevance
“…Phenotypic variation in metamorphic phenotype was similar to the variation observed in other field March 2012 663 FROM METAMORPHOSIS TO MATURITY studies (Smith 1987, Semlitsch et al 1988). The previously described positive phenotypic correlations between metamorphic, juvenile, and adult life-history traits (Smith 1987, Semlitsch et al 1988, Berven 1990, Goater 1994, Scott 1994, Morey and Reznick 2001, Altwegg and Reyer 2003, Chelgren et al 2006 were only confirmed when we looked at one trait at a time. Yet, because disadvantages in one trait can be cancelled out by other traits (Dobzhansky 1956), more integrative fitness measures, such as the probability to reach maturity and population growth rate, are necessary (McPeek and Peckarsky 1998).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Phenotypic variation in metamorphic phenotype was similar to the variation observed in other field March 2012 663 FROM METAMORPHOSIS TO MATURITY studies (Smith 1987, Semlitsch et al 1988). The previously described positive phenotypic correlations between metamorphic, juvenile, and adult life-history traits (Smith 1987, Semlitsch et al 1988, Berven 1990, Goater 1994, Scott 1994, Morey and Reznick 2001, Altwegg and Reyer 2003, Chelgren et al 2006 were only confirmed when we looked at one trait at a time. Yet, because disadvantages in one trait can be cancelled out by other traits (Dobzhansky 1956), more integrative fitness measures, such as the probability to reach maturity and population growth rate, are necessary (McPeek and Peckarsky 1998).…”
Section: Discussionmentioning
confidence: 55%
“…As previous studies showed, performance in the larval aquatic environment, as measured by the metamorphic phenotype, is likely to affect performance in later terrestrial stages. This relationship is not universal, however, or it may be limited to a short period of time (McPeek and Peckarsky 1998, Boone 2005, De Block and Stoks 2005, Chelgren et al 2006. In amphibians, long periods of post-metamorphic growth are the rule; maturity is often delayed and attained at different ages by individuals from the same cohort (Bell 1977, Werner 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Land cover may subject F. limnocharis to more biological interactions, such as predation, and environmental stresses, such as desiccation. Desiccation has been noted to be prevalent in small‐bodied amphibians that try to pass through different land cover types due to erratic environmental conditions (Becker, Fonseca, Haddad, Batista, & Prado, 2007; Chelgren, Rosenberg, Heppell, & Gitelman, 2006; Tracy, Christian, & Tracy, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Body size of frogs at metamorphosis is an important determinant for adult fitness, and larger body weights may enable frogs a greater ability to escape predation, seek out new territories, and mate more successfully [30,31]. A possible corollary of reduced growth in frogs to human health is low birth weight.…”
Section: Discussionmentioning
confidence: 99%